Spontaneous remission of nephrotic syndrome in HUS-TTP - (:unkn) unknown (My University, 2003)
We report a three-year-old girl with thrombotic microangiopathy, severe encephalopathy and nephrotic syndrome. She presented with encephalopathy, oliguria and edema with laboratory findings of thrombocytopenia, anemia, heavy proteinuria, and elevated liver enzymes and blood urea nitrogen. The encephalopathy lasted for 7 days where as the nephrotic syndrome lasted for over a month. Hemolytic uremic syndrome (HUS) - thrombotic thrombocytopenic purpura (TTP) with severe neurological involvement and nephrotic syndrome that improved without any sequelae was discussed.
Keywords: Central nervous system involvement; Encephalopathy; HUS-TTP; Nephrotic syndrome